Pembinaan Kelompok Masyarakat Pemulung Dalam Pembuatan Teluk Pabokabe (Teknik Lukis Pada Botol Kaca Bekas) Dengan Menerapkan Ornament Batak Toba Sebagai Elemen Interior Ruangan Di Kelurahan Paya Pasir Medan Marelan Sumatera Utara - Rosramadhana, Rosramadhana; Aricindy, Argitha; Siregar, Purnama Sari; Loviarara, Jennica; Maulina, Dinna (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
At this time there are a lot of garbage which is getting more and more increasing every day, such as the numberof used glass bottles which are also increasing in number. This problem is both a challenge and an opportunity for thePKM-M team to carry out service activities in the field of community empowerment in the village 01 Paya Pasir MedanMarelan North Sumatra. This activity aims to provide understanding to the community to utilize used glass bottles as adecoration of interior elements by using painting techniques and adding Toba Batak ornaments and motifs to the glassbottle. The activity began with a visit by the PKM-M team accompanied by a supervisor, then the PKM-M Teamcooperated with the Kelurahan management for technical implementation. The implementation method used includes twomajor things: the preparation stage and the core stage. The results of the implementation that have been achieved are allsessions in the preparation and core programs of socialization, inauguration, core activities and evaluation of activitieshave been carried out well. The indicator that has been reached is that the community has understood and is able to makethe Teluk Pabokabe and planned to be further developed